Pelatihan Penyusunan Modul Pembelajaran Digital Menggunakan Aplikasi Heyzine - Sari, Dian Ratna; Fathimah, Ismah; Meriza, Nadya; jalmo, Tri (Universitas Lampung, 2024)
Advances in technology and information in the world of education provide opportunities for the development of digital learning modules. Digital learning modules are used as an interesting and interactive learning media for students. Skills in compiling digital learning modules need to be trained for students, especially prospective educators in the future. On the other hand, access to the preparation of contextual digital learning modules is still very limited. In order to overcome these potentials and problems, training has been carried out in preparing digital learning modules using the Heyzine application through the Community Service program. This training is aimed to increase skills for prospective teacher students, especially biology education, in compiling digital learning modules. The method used consists of Planning, Organizing, Actuating, Controlling and Evaluating. The results of the training have helped prospective teacher students improve their skills in compiling digital modules and provided opportunities for students to be creative in designing other digital learning media.Keywords: digital learning modules; heyzine; training AbstrakKemajuan teknologi dan informasi di dunia pendidikan memberi peluang pada pengembangan modul pembelajaran digital. Modul pembelajaran digital dimanfaatkan sebagai media pembelajaran yang menarik dan interaktif bagi peserta didik. Keterampilan menyusun modul pembelajaran digital perlu dilatih untuk mahasiswa khususnya calon pendidik di masa mendatang. Di sisi lain, akses dalam penyusunan modul pembelajaran digital yang kontekstual masih sangat terbatas. Dalam rangka mengatasi potensi dan masalah tersebut, telah dilakukan pelatihan penyusunan modul pembelajaran digital menggunakan aplikasi Heyzine melalui program Pengabdian Kepada Masyarakat. Pelatihan ini ditujukan untuk meningkatkan keterampilan kepada mahasiswa calon guru khususnya pendidikan biologi dalam menyusun modul pembelajaran digital. Metode yang dilakukan terdiri dari Planning, Organizing, Actuating, Controlling dan Evaluating. Hasil dari pelatihan telah membantu mahasiswa calon guru dalam meningkatkan keterampilan menyusun modul digital serta memberikan peluang bagi mahasiswa untuk berkreativitas dalam merancang media pembelajaran digital lainnya.Kata Kunci: heyzine; modul pembelajaran digital; pelatihan DOI: https://doi.org/10.23960/rp/v4i2.hal.32-38